2017
DOI: 10.1145/3134685
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Support Seeking from Peers for Pregnancy in Online Health Communities

Abstract: We report a study of peer support in online health communities for pregnancy care along three gestational stages (trimesters) to investigate how pregnant women seek and receive peer support during different stages of pregnancy. Using Babycenter.com as our research setting, we found that pregnant women sought peer support due to constrained access to healthcare providers, dissatisfaction with healthcare services/medical advice, limited offline social support, and unavailability of information in other venues. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
78
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 43 publications
10
78
0
7
Order By: Relevance
“…Aside from the topic relating to childbirth, which is analogous to our "labor" topic, the remaining topics either did not arise in our findings (i.e, fetal development) or were not dominant in specific trimesters. The topics found in our study, however, are largely similar to those from Gui et al (2017), who analyzed trimester-specific forums on BabyCenter.com, and overlap to some extent with a study examining pregnant women's search queries [28].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Aside from the topic relating to childbirth, which is analogous to our "labor" topic, the remaining topics either did not arise in our findings (i.e, fetal development) or were not dominant in specific trimesters. The topics found in our study, however, are largely similar to those from Gui et al (2017), who analyzed trimester-specific forums on BabyCenter.com, and overlap to some extent with a study examining pregnant women's search queries [28].…”
Section: Discussionsupporting
confidence: 53%
“…The sheer amount of data on these pregnancy forums offers a unique, untapped opportunity to examine how women seek online information from a community of peers during pregnancy. To our knowledge, the only prior general empirical study on these forums was conducted by Gui et al (2017), who examined 200 online posts in each of three trimester-specific BabyCenter.com forums, utilizing a grounded theory research design [29]. Gui et al (2017) found that women sought advice, informal and formal knowledge, reassurance, and emotional support; they also identified specific topics of support-seeking across the three trimesters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these technologies have been designed to communicate healthrelated information to parents [86]. HCI researchers have developed prototype applications for Dutch (Babywijzer), Pakistani (Baby+), and Vietnamese Australian (We-HELP) populations [70,78,92], deployed SMS-based systems for personalised health information communication in Kenya and Pakistan [8,63] and conducted qualitative analyses of pregnant women's motivations for information sharing and support seeking online [29,43,65]. Peyton et al propose a 'pregnancy ecology,' comprising physical, emotional, informational and social supports, to support the design of physical health interventions [64], which Prabhakar et al extend to include support needs, sources, and interventions within an Evolving Ecology of Support [66].…”
Section: Related Work Mobile Technologies For Perinatal Wellbeingmentioning
confidence: 99%